Pemberdayaan Kelompok Peduli Ginjal (Poklinjal) Dalam Pencegahan Penyakit Gagal Ginjal Kronis - Handoyo, Handoyo; Hartati, Hartati; Prasetyo, Herry (Universitas Jenderal Soedirman, Jurusan Keperawatan, 2025)
The kidneys are organs that function to maintain blood composition, control the balance of body fluids and electrolytes and the production of hormones and enzymes that control blood pressure. Through education and updating information about kidney health, it is hoped that the incidence and mortality rate of chronic kidney disease in the community can be reduced. The purpose of this community service is to improve the knowledge and skills of health cadres about preventing chronic kidney disease in all age groups in the community. The community service method is carried out by providing education about kidney health through lectures and interactive discussions. Assistance and monitoring of activities are carried out by the community service team. The results of the evaluation of the implementation of the activity showed an increase in the number of respondents who scored well from 2 (6.6%) during the pre-test to 25 respondents (83.3%) in the post-test. This shows an increase in the percentage of respondents who scored well in the pre- and post-test sessions by 76.7%.